Financial Inclusion and Financial Literation for ‘Laku Pandai’ Customers - Slamet, Achmad; Yulianto, Arief; Ridloah, Siti; Abiprayu , Kris Brantas (KnE Social Sciences, 2019)
Thepurposeofthisstudyistodeterminethelevelofﬁnancialliteracyandtheimpactof ﬁnancialliteracyondecisionsonaccessanduseofﬁnancialservicesfor‘LakuPandai’ customers. The primary data used is from ‘Laku Pandai’ customers in Semarang City, Central Java Province. Data analysis using logit regression, with the scale of interval data on ﬁnancial literacy is the interval. Whereas, the scale of the data on ﬁnancial inclusionisnominal.Theresultsofthestudyindicatethatﬁnancialliteracywillincrease theprobabilityof1time inusing bankingaccessandservices.Thisisbecause banking information has been conveyed to ‘Laku Pandai’ customers. Thus, supply side or ﬁnancial inclusion is not solely caused by ﬁnancial literacy, but rather by information provided by banks to ‘Laku Pandai’ customers. Keywords: financial inclusion, financial literation, Laku Pandai customers.